Membangun Berpikir Kreatif Dalam Berwirausaha Melalui Pendekatan Psikologi Positif - Muh. Fitrah Ramadhan Umar; Rosdiana Ngitung; Imul Nadir Kasim (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Many campuses currently include entrepreneurship courses to prepare their students when they graduate when they want to become entrepreneurs. In this entrepreneurship course, students are sometimes asked to run business processes. The obstacle that students often get in carrying out this business process is finding creative ideas. This is important because through this creative idea students can find business ideas that they will run. The solution to this problem is to incorporate positive psychological approaches when doing creative thinking. This paper aims to determine the relationship between positive psychology and creative thinking in students who are entrepreneurship. This paper uses the literature review method by collecting related articles and books. The result of this paper is that a positive psychological approach can help students think creatively in finding business ideas that they will run.